Building strength, endurance, and mobility using an astaxanthin formulation with functional training in elderly. Issue 5 (26th September 2018) - Liu, Sophia Z.; Ali, Amir S.; Campbell, Matthew D.; Kilroy, Kevin; Shankland, Eric G.; Roshanravan, Baback; Marcinek, David J.; Conley, Kevin E.
Abstract: Background: Building both strength and endurance has been a challenge in exercise training in the elderly, but dietary supplements hold promise as agents for improving muscle adaptation. Here, we test a formulation of natural products (AX: astaxanthin, 12 mg and tocotrienol, 10 mg and zinc, 6 mg) with both anti‐inflammatory and antioxidant properties in combination with exercise. We conducted a randomized, double‐blind, placebo‐controlled study of elderly subjects (65–82 years) on a daily oral dose with interval walking exercise on an incline treadmill. Methods: Forty‐two subjects were fed AX or placebo for 4 months and trained 3 months (3×/week for 40–60 min) with increasing intervals of incline walking. Strength was measured as maximal voluntary force (MVC) in ankle dorsiflexion exercise, and tibialis anterior muscle size (cross‐sectional area, CSA) was determined from magnetic resonance imaging. Results: Greater endurance (exercise time in incline walking, >50%) and distance in 6 min walk (>8%) accompanied training in both treatments. Increases in MVC by 14.4% (±6.2%, mean ± SEM, P < 0.02, paired t ‐test), CSA by 2.7% (±1.0%, P < 0.01), and specific force by 11.6% (MVC/CSA, ±6.0%, P = 0.05) were found with AX treatment, but no change was evident in these properties with placebo treatment (MVC, 2.9% ± 5.6%; CSA, 0.6% ± 1.2%; MVC/CSA, 2.4 ± 5.7%; P > 0.6 for all). Conclusions: The AX formulation improved muscle strength and CSA in healthy elderly in addition to the elevation in endurance and walking distance found with exercise training alone. Thus, the AX formulation in combination with a functional training programme uniquely improved muscle strength, endurance, and mobility in the elderly.